Perubahan Peran Perempuan di PTPN VII Pabrik Gula Cinta Manis Di Kabupaten Ogan Ilir - Pahurian, Putri (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
The title of this paper is "the change in the role of women in ptpn vii sugar factory in Cinta manis ogan ilir district" The focus of this research is to explain the changes in the function and role of women in the Cinta Manis sugar factory, in line with changes in village conditions that occur due to changes from the agricultural to industrial areas. The focus of this research also wants to see and explain where the function of women is like and about the role of women laborers who perform two roles at once, namely in the domestic and public sectors as well as power relations between men and women in industrial societies in the sweet love sugar factory. The method used in this study is a qualitative research method. This research source is primary data taken directly from the field through interviews with informants from women felling laborers. Secondary data obtained from documentation, books or journals. The techniques used in data collection are observation, interviews and documentation. The results obtained in this study are the first, Ketiau Village before the entry of the Cinta Manis sugar factory, the community's work in this village is a farmer and trader, but more dominant farmers. After the entry of the sugar factory in this village also experienced changes in terms of livelihoods, many people who worked as employees or as factory workers, who worked in the factory and even then not only from the Ketiau area but from outside the area also many who worked at the company. Second, there are many women in this factory who work as sugar cane cutting laborers. What makes women come to work is by economic factors, because if you rely on your husband alone can not meet their needs. The role of the fostering also changed, which usually played the role of a housewife but now works, women workers in the factory must perform two roles at the same time. Third, women only live and obey what has been determined by culture. Culture that distinguishes the roles of men and women. Clearly this culture has assumed a man's position higher than a woman's. The culture referred to here is patriarchal culture, patriarchal culture is defined as a dominant culture that is male, or the ruling is male, as in terms of earning a living a man not a woman. But in PTPN VII Sugar Factory, this culture is no longer valid because at this time everything has changed, the views or thoughts of a person have developed, in terms of earning a living not only a man can but a woman can also make a living, like as well as female slave laborers in the Cinta Manis Sugar Factory.